Penerapan Sistem Hazard Analysis Critical Control Point (HACCP) pada Produk Banana Cake di Aerofood ACS Surabaya - Annisa Salsabila Setya Budi; Trias Mahmudiono (Amerta Nutrition, 2021)
ABSTRACTBackground: Aerofood ACS Surabaya as an international inflight catering service is required to have good food safety standards to ensure the quality of the products. The food safety system implemented by Aerofood ACS Surabaya on all its product is Hazard Analysis Critical Control Point (HACCP), including the banana cake. HACCP needs to be applied to prevent the possibility of physical, chemical, and biological contamination on food product that can cause foodborne disease.Objectives: The purpose of this research is to identify the application of HACCP system to banana cake in Aerofood ACS Surabaya.Methode: The method of this research is a qualitative descriptive method including field observation, interviews, and analyzes HACCP documents of aerofood ACS Surabaya.Result: There are 18 steps to produce banana cake until it can distributed to airlines and can be consumed by consumers: receiving of eggs, receiving of banana, receiving of dry goods (flour, sugar, baking soda, and oil), eggs storage, banana storage, dry goods storage, egg cracking, flour sifting, weighing, mixing, baking, chilling, shaping, packaging, storage of banana cake, setting in the tray, holding room, and delivery to plane. From 18 steps to produce banana cake, there are six critical control points: receiving of eggs, eggs storage, baking, cooling, storage of banana cake, and holding room.Conclusions: Physical, chemical, and biological contamination on banana cake can be prevented by paying attention to each steps, especially the critical control point. Aerofood ACS Surabaya has implemented the HACCP system properly and accordance with the established HACCP plan.Keywords: HACCP, food safety, airlines catering service, foodborne diseaseABSTRAKLatar Belakang: Aerofood ACS Surabaya sebagai perusahaan jasa boga penerbangan bertaraf internasional diharuskan memiliki standar keamanan pangan yang baik untuk menjamin mutu produk yang dihasilkan. Sistem keamanan pangan yang diterapkan oleh Aerofood ACS Surabaya pada semua produknya adalah Hazard Analysis Critical Control Point (HACCP), termasuk pada banana cake. HACCP perlu diterapkan untuk mencegah kemungkinan kontaminasi fisik, kimia, dan biologi pada produk pangan yang dapat menyebabkan foodborne disease.Tujuan: Tujuan penelitian ini adalah untuk mengidentifikasi penerapan sistem HACCP pada produk banana cake di Aerofood ACS Surabaya.Metode: Metode dari penelitian ini adalah metode deskriptif kualitatif yang meliputi observasi lapangan, wawancara, dan menganalisis dokumen HACCP Aerofood ACS Surabaya.Hasil: Terdapat 18 tahap produksi banana cake hingga produk dapat didistribusikan ke peswat dan dapat dinikmati oleh konsumen, yaitu penerimaan telur, penerimaan buah pisang, penerimaan bahan baku kering (tepung, gula, baking soda, dan minyak), penyimpanan telur, penyimpanan buah pisang, penyimpanan bahan baku kering, pemecahan telur, pengayakan tepung, penimbangan, mixing, baking, pendinginan, pembentukan, pengemasan, penyimpanan banana cake, penataan pada tray, penyimpanan pada holding room, dan delivery ke pesawat. Dari 18 tahap produksi banana cake, terdapat enam titik kritis yaitu penerimaan telur, penyimpanan telur, baking, pendinginan, penyimpanan banana cake, dan penyimpanan pada holding room.Kesimpulan: Kontaminasi fisik, kimia, dan biologi pada produk banana cake dapat dicegah dengan memerhatikan setiap langkah terutama titik kritis. Aerofood ACS Surabaya telah melaksanakan sistem HACCP dengan baik dan sesuai dengan HACCP plan yang telah ditetapkan.Kata Kunci: HACCP, keamanan pangan, jasa boga penerbangan, foodborne disease